LIFE COURSE CRIME THEORIES AND THEIR CONTRIBUTION TO THE CRIMINOLOGY FIELD - Murat Gozubenli; Mehmet Unal (European Scientific Journal, ESJ, 2014)
Early studies revealed that a relatively few “chronic” individuals are responsible for the majority of all reported violent and property offenses. Further research on individual career criminals gave birth to “life course criminology”, which try to explain why certain individuals continue on or desist from deviant behavior. In this context, this study aims to give brief introduction about the life course theories, their presumptions and their enduring value for the field of criminology.